Simulation Study of the Grinding Machining Deformation of Large Gear Ring - Liu Linhui; Yang Long; Zhang Jian; Chen Xiao; An Wendi (Jixie chuandong)
Large gear ring forming grinding is the key technology to ensure the quality of ring gear processing. Forming grinding will produce grinding force and a lot of heat,causing grinding deformation. With the help of the engineering software Hypermesh,Matlab and ANSYS,based on the grinding contact area model,the grinding force model and the grinding and moving heat source theory,the simulation process of deformation prediction under the action of gear ring grinding is analyzed. Taking the large gear ring as an example,the grinding area,the grinding force and the heat flow rate are calculated,and the finite element model of the forming grinding of the gear ring is established. The numerical simulation of the grinding field and the deformation field of the gear ring are obtained. The prediction of temperature field and deformation of gear ring forming grinding process has certain guiding significance to improve the machining precision of gear ring forming.